Resiliensi Pengrajin Gula Aren di Kabupaten Bulukumba (Studi Kasus Desa Anrihua Kecamatan Kindang) - Helda Ibrahim; Adriyanti Syam; Musdalifah Mahmud; Majdah Muhyddin Zain (Fakultas Pertanian Universitas Ichsan Gorontalo, 2023)
Anrihua Village is one of the villages in Kindang subdistrict, Bulukumba district which has the potential to produce palm sugar of the best quality. Changes in the business system both from social, cultural, and economic aspects as well as the characteristics of palm sugar craftsmen require a continuous process. The objectives of this research are: 1) To determine the characteristics of palm sugar craftsmen in Anrihua Village, Kindang District. 2) To find out the process of making palm sugar in Anrihua Village, Gantarang District. 3) To analyze the resilience of palm sugar craftsmen from social, cultural, and economic aspects in Anrihua Village, Kindang District. This research was carried out in July – August 2023. This research was conducted in Anrihua Village, Kindang District, Bulukumba Regency, South Sulawesi Province. The population and sample in this study were taken by census, namely 33 palm sugar craftsmen. The results of this research show that the identity of palm sugar craftsmen in Anrihua Village is that the age of productive palm sugar craftsmen is 36 years to 57 years. Palm sugar craftsmen are dominated by women. The education of most palm sugar craftsmen is only in elementary school (SD). palm sugar in Anrihua Village ranges from 3 years to 12 years and the number of dependents of palm sugar craftsmen in the family ranges from 1 person to 4 people. The process of making palm sugar in Anrihua Village, Kindang subdistrict is still simple and traditional. The resilience of palm sugar craftsmen from 33 respondents shows the value of the social aspect with a percentage of 53% (Less Resistance), the cultural aspect with a percentage of 66% (Surviving), and the economic aspect with a percentage of 64% (Surviving).